A theoretical framework for the study of compression sensing in ionic polymer metal composites - Valentina Volpini; Lorenzo Bardella; Andrea Rodella; Cha Youngsu; Maurizio Porfiri (ELECTROACTIVE POLYMER ACTUATORS AND DEVICES (EAPAD) 2017, 2017)
Ionic Polymer Metal Composites (IPMCs) are electro-responsive materials for sensing and actuation, consisting of an ion-exchange polymeric membrane with ionized units, plated within noble metal electrodes. In this work, we investigate the sensing response of IPMCs that are subject to a through-the-thickness compression, by specializing the continuum model introduced by Cha and Porfiri,1 to this one-dimensional problem. This model modifies the classical Poisson-Nernst-Plank system governing the electrochemistry in the absence of mechanical effects, by accounting for finite deformations underlying the actuation and sensing processes. With the aim of accurately describing the IPMC dynamic compressive behavior, we introduce a spatial asymmetry in the properties of the membrane, which must be accounted for to trigger a sensing response. Then, we determine an analytical solution by applying the singular perturbation theory, and in particular the method of matched asymptotic expansions. This solution shows a good agreement with experimental findings reported in literature.
Keywords: Ionic polymer metal composites; finite deformations; sensing; null; multiphysics; null; electrochemistry; null; matched asymptotic expansions